Le « roman scientifique » en Chine : prémices d’une science-fiction instrumentalisée - Loïc Aloisio (ReS Futurae)
This paper aims to explain, through an historical review, how the science fiction genre was introduced in China, which role has been given to it from the very beginning, in order to understand the place of this literary genre in the Chinese society from the late Qing period (1860-1911) to nowadays. To this end, this article engages in thematic and poetic analyses of the main novels published between 1860 (the introduction of western science in China) and 1911 (fall of the Qing dynasty) to highlight the hopes and ideals which have been given to the genre in China. This paper also explores the historical background in which this literary genre was introduced, and also the diverse influences received by these authors. Then, it examines the theoretical writings published at this time, which can give us a better understanding of the instrumentalization of this genre in Mainland China. This article intends to raise the issue of the impact of this nascent literary genre on the later science fiction writings in the Middle Kingdom, which can help us in the study and the comprehension of the genre today and its future in China.